2021
DOI: 10.1186/s12884-020-03355-3
|View full text |Cite
|
Sign up to set email alerts
|

Birthweight: EN-BIRTH multi-country validation study

Abstract: Background Accurate birthweight is critical to inform clinical care at the individual level and tracking progress towards national/global targets at the population level. Low birthweight (LBW) < 2500 g affects over 20.5 million newborns annually. However, data are lacking and may be affected by heaping. This paper evaluates birthweight measurement within the Every Newborn Birth Indicators Research Tracking in Hospitals (EN-BIRTH) study. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 32 publications
0
43
1
Order By: Relevance
“…Readmissions to KMC ward/corners could inflate KMC coverage and this needs further consideration. Defining the denominator for routine HMIS tracking will be critical, especially since LBW rate (≤2499 g) is already a core 100 health indicator but the KMC clinical need definition is currently ≤2000 g. Also the subtle definition differences of excluding babies weighing exactly 2500 g for LBW indicator, yet including those weighing 2000 g for KMC indicator adds a dimension of measurement complexity from aggregated routine data [30]. In Tanzania the national policy for KMC includes all LBW babies and in our study hospitals' KMC wards we found 3% of our sample had admission weights > 2000 g. We collected KMC ward/corner admission weight for consistency, but notably mean age of admission varied by hospital, affecting the relationship between birth and admission weight.…”
Section: Register Data Usementioning
confidence: 99%
See 1 more Smart Citation
“…Readmissions to KMC ward/corners could inflate KMC coverage and this needs further consideration. Defining the denominator for routine HMIS tracking will be critical, especially since LBW rate (≤2499 g) is already a core 100 health indicator but the KMC clinical need definition is currently ≤2000 g. Also the subtle definition differences of excluding babies weighing exactly 2500 g for LBW indicator, yet including those weighing 2000 g for KMC indicator adds a dimension of measurement complexity from aggregated routine data [30]. In Tanzania the national policy for KMC includes all LBW babies and in our study hospitals' KMC wards we found 3% of our sample had admission weights > 2000 g. We collected KMC ward/corner admission weight for consistency, but notably mean age of admission varied by hospital, affecting the relationship between birth and admission weight.…”
Section: Register Data Usementioning
confidence: 99%
“…Disaggregating by admission weight may be complex due to regaining of weight that newborns lose immediately after birth. Birthweight may not be available for outborns or be heaped for inborns [30]. Individual longitudinal data linking KMC monitoring of outcome, nutrition and development is already a reality in the most established KMC national programmes [34].…”
Section: Register Data Usementioning
confidence: 99%
“…Women's survey-report performed fairly well for birthweight, although with more heaping than in register data [24]. EN-BIRTH shows for the first time that such surveys may be a useful tool for capturing information on contact indicators, such as admission to a neonatal unit [23] or KMC ward.…”
Section: What Is New and What Have We Learned?mentioning
confidence: 93%
“…Subsequent papers detail findings for the following maternal and newborn coverage indicators: uterotonics to prevent postpartum haemorrhage [18], immediate newborn care including breastfeeding practices [19], chlorhexidine for umbilical cord care [20], neonatal resuscitation [21], KMC [22], neonatal infection antibiotic management [23]. Two papers assess validity and data quality for the outcomes of birthweight [24] and stillbirth [25]. Measurement of respectful maternal and newborn care is assessed in one site (Nepal) [26].…”
Section: What Is New and What Have We Learned?mentioning
confidence: 99%
See 1 more Smart Citation